Exploiting node mobility for fault management in RPL-based wireless sensor networks. (2018) - Bendouda, Djamila; Mokdad, Lynda; Haffaf, Hafid
This paper aims to propose an effective new local repair technique with RPL protocol in WSNs. To replace node failure by the mobility of their predecessor without rebuilding the RPL tree, is a new proposed solution with MN-LR_RPL method. In addition, RPL was originally designed for static networks, with no support for mobility. However, handling the local repair mechanism for the RPL with mobile nodes is a real challenge. Our work is the first effort implemented for fault management using MN-LR_RPL that is presented by an algorithm which is simulated using COOJA with Contiki OS. The performance evaluation results show that MN-LR_RPL allows a great improvement when compared to the standard specification in cases of local repair, mainly in terms of packet loss ratio and average network latency. Based on our new solution, we offer a few suggestions for using wireless software defined network (WSDN) to improve RPL protocol in IoT.